Detection of Pb in Whitening Creams via Laser Induced Breakdown Spectroscopy - Bidin, Noriah B (JOURNAL OF ADVANCES IN PHYSICS, 2013)
<!-- [if gte mso 9]> <![endif]--> <span style="font-size: 12.0pt; line-height: 115%; font-family: 'Times New Roman','serif'; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-MY; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Recently whitening creams have been widely used to protect UV light exposure due to the depletion of ozone layer. The demand attracts the rapid growth of various whitening creams in the market. The detection is required in order to determine the constituent of the whitening cream, whether it contains dangerous element like heavy metal (Pb, Hg or Cr). In this attempt, laser induced breakdown spectroscopy (LIBS) technique was deployed to analyse the existence of heavy metal. Several whitening creams available in retail shop and open market were investigated. Cryogenically frozen technique was utilized to convert the emulsion into solid form. Lead Pb was detected in all the tested samples in the range of 2 - 5 ppm. The LIBS results were validated by Inductive Couple Plasma Mass Spectroscopy (ICP-MS) technique. The high sensitivity, portable and in-situ LIBS system allow simple, faster and easy heavy metal detection. This enhances the procedure of inspection in cosmetic industries <!-- [if gte mso 9]> Normal 0 false false false EN-MY X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->